Identification of Timeliness of Anti-Tuberculosis Drug Intake and Pulmonary Tuberculosis Cure Rate at An-Nisa Hospital - Adi Dwi Susanto; Muhamad Martono Diel (JURNAL CITRA KEPERAWATAN, 2026)
Tuberculosis (TB) is the third leading cause of death across all age groups in Indonesia, as well as the leading cause of death from infectious diseases, with treatment success highly dependent on patient adherence, particularly the timeliness of anti-tuberculosis drug intake. This study aims to identify the relationship between medication timing adherence and the level of recovery among pulmonary TB patients at An-Nisa Hospital. This study employed a quantitative method with a cross-sectional approach. The study population consisted of tuberculosis patients who had undergone treatment at An-Nisa Hospital for six months. A total of 108 respondents were selected using an accidental sampling technique. The study was conducted in August 2025 over a period of two weeks at An-Nisa Hospital. Data were collected using a questionnaire. Data analysis using Spearman rank test. The findings demonstrated a statistically significant and moderate positive relationship between the timeliness of anti-tuberculosis drug intake and the pulmonary tuberculosis cure rate at An-Nisa Hospital (p = 0.000; r = 0.490). This study found a statistically significant and moderate positive relationship between the timeliness of anti-tuberculosis drug intake and the cure rate of pulmonary tuberculosis at An-Nisa Hospital.